Are females who inject drugs at higher risk for HIV infection than males who inject drugs: an international systematic review of high seroprevalence areas - Des Jarlais, Don C (2012)
OBJECTIVE: There are multiple reasons why females who inject drugs may be more likely to become infected with HIV than males who inject drugs. Where this is the case, special HIV prevention programs for females would be needed. DESIGN: International systematic review and meta-analysis of studies across 14 countries. METHODS: Countries with high seroprevalence (>20%) HIV epidemics among persons who inject drugs (PWID) were identified from the Reference Group to the UN on HIV and Injecting Drug Use. Systematic literature reviews collected data on HIV prevalence by gender for these countries. Non-parametric and parametric tests along with meta-analytic techniques examined heterogeneity and differences in odds ratios (OR) across studies. RESULTS: Data were abstracted from 117 studies in 14 countries; total sample size N=128,745. The mean weighted OR for HIV prevalence among females to males was 1.18 [95% CI 1.10–1.26], with high heterogeneity among studies (I(2) = 70.7%). There was a Gaussian distribution of the log ORs across studies in the sample. CONCLUSION: There was a significantly higher HIV prevalence among females compared to males who inject drugs in high seroprevalence settings, but the effect size is extremely modest. The high level of heterogeneity and the Gaussian distribution suggest multiple causes of differences in HIV prevalence between females and males, with a specific difference determined by local factors. Greater understanding of factors that may protect females from HIV infection may provide insights into more effective HIV prevention for both females and males who inject drugs.